1978
DOI: 10.1113/jphysiol.1978.sp012374
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of excitatory junctional potentials recorded from arterioles.

Abstract: 1. Arterioles were impaled with two independent micro-electrodes, one to pass current and the other to record membrane potential. 2. When current was injected into one branch of an arteriole, a membrane potential change could be detected either in the same branch or in an adjoining branch indicating that the arteriolar smooth muscle cells were electrically connected. 3. Fine dissection of the arteriolar tree gave short segments of arteriole which appeared to behave electrically as short cables with sealed ends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
194
2
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(217 citation statements)
references
References 17 publications
20
194
2
1
Order By: Relevance
“…Because many observations have revealed an exponential decay of the conducted electrical signal, it was proposed that longitudinal spread of vasomotor responses reflects the passive, electrotonic conduction of changes in membrane potential via gap junctions connecting cells of the vessel wall (Pacicca et al, 1996;Welsh & Segal, 1998;Gustafsson & Holstein-Rathlou, 1999). Therefore, the decay of the conducted vasomotor responses along the vessel length should be consistent with the length constant estimated from electrotonic potentials produced by current injection into the smooth muscle or endothelial cells of arterioles, which is between 0.9 and 1.6 mm (Hirst & Neild, 1978;Hirst et al, 1997;Emerson et al, 2002).…”
Section: Conduction Of Vasomotor Responsesmentioning
confidence: 94%
“…Because many observations have revealed an exponential decay of the conducted electrical signal, it was proposed that longitudinal spread of vasomotor responses reflects the passive, electrotonic conduction of changes in membrane potential via gap junctions connecting cells of the vessel wall (Pacicca et al, 1996;Welsh & Segal, 1998;Gustafsson & Holstein-Rathlou, 1999). Therefore, the decay of the conducted vasomotor responses along the vessel length should be consistent with the length constant estimated from electrotonic potentials produced by current injection into the smooth muscle or endothelial cells of arterioles, which is between 0.9 and 1.6 mm (Hirst & Neild, 1978;Hirst et al, 1997;Emerson et al, 2002).…”
Section: Conduction Of Vasomotor Responsesmentioning
confidence: 94%
“…Conducted responses may form the base for spatial coordination of local vasomotor responses 2. Conduction of both vasoconstriction and vasodilation in vascular networks has been described,3 and the mechanisms through which these occur are subject of ongoing studies. It has been shown that changes in membrane potential (hyper‐ or depolarization) resulting from local stimuli can propagate intercellularly mainly along the endothelial cells, but also along the smooth muscle cell layers of arteries 4.…”
Section: Introductionmentioning
confidence: 99%
“…A blood vessel can be approximated from the electrical point of view as a cable with certain membrane and internal conductances [146,161]. In a passive linear cable with infinite length, the steady-state spread of a local potential change is attenuated exponentially:…”
Section: Length Constantsmentioning
confidence: 99%
“…The vessel model was reduced to two dimensions (axial and radial) on the assumption that concentration and potential gradients in the circumferential direction are negligible [147]. These gradients should be minimal during circumferentially uniform stimulations, but are small even during local stimulation with an intracellular microelectrode [146]. In this study we assume that an EC spans 15 SMCs and vice versa.…”
Section: Multicellular Vessel Modelmentioning
confidence: 99%
See 1 more Smart Citation